ANTIBIOTIC RESISTANCE OF ESCHERICHIA COLI ISOLATED FROM PATIENTS IN SHAHID SADOUGHI HOSPITAL, YAZD, IRAN - Jamshid Ayatollahi; Seyed Hossein Shahcheraghi et al. (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVES: The enhancement of antibiotic resistance has been ascribed to a collection of microbial characteristics, the selective pressure of antibiotic use and social and technical vicissitudes that enhance the transmission of resistant organisms.The aim of this study was to investigate antimicrobial-resistance to Escherichia coli isolated from patients in Shahid Sadoughi hospital of Yazd. METHODS: Antimicrobial susceptibility to ceﬁxime, cefotaxime, ceftazidime, ceftriaxone, ciproﬂoxacin, gentamicin, imipenem, cotrimaxazole and nalidixic acid was determined for 492 E. coli isolates obtained from patients in Shahid Sadoughi hospital of Yazd in 2012. RESULTS: In this study, imipenem was the most active agent (70.1% susceptible), followed by gentamicin and ciproﬂoxacin. High rates of resistance were observed to nalidixic acid (69.9%) and cotrimoxazole (62.2%). CONCLUSIONS: The investigation of antimicrobial susceptibility is essential, and will help to identify E. coli resistance to antimicrobial agents and attempt to limit its spread